2020
DOI: 10.1186/s12885-020-07108-5
|View full text |Cite
|
Sign up to set email alerts
|

PODXL might be a new prognostic biomarker in various cancers: a meta-analysis and sequential verification with TCGA datasets

Abstract: Background: Several studies have investigated the associations between the podocalyxin-like protein (PODXL) expression quantity or locations and cancers survival, but the results were far from conclusive. Therefore, we proceeded a meta-analysis on PODXL in various human cancers to find its prognostic value and followed confirmation using the TCGA datasets. Methods: We performed a systematic search, and 18 citations, including 5705 patients were pooled in metaanalysis. The results were verified with TCGA datase… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 51 publications
1
13
0
Order By: Relevance
“…Podocalyxin-like protein is a member of CD34 family proteins, which carries numerous post-translational epitopes responsible for various kinds of pluripotent surface biomarkers, including TRA-1-60, mAb84, TRA-1-81, GP200, and GCTM2 (Kang et al, 2016). It is also associated with more than 10 human malignancies (Kang et al, 2016;He et al, 2020). These studies suggest that PODXL may be responsible for the impaired proliferative activity of SSC by TCF3 silencing.…”
Section: Podxl Is a Direct Target Of Tcf3 In Human Sscsmentioning
confidence: 83%
See 1 more Smart Citation
“…Podocalyxin-like protein is a member of CD34 family proteins, which carries numerous post-translational epitopes responsible for various kinds of pluripotent surface biomarkers, including TRA-1-60, mAb84, TRA-1-81, GP200, and GCTM2 (Kang et al, 2016). It is also associated with more than 10 human malignancies (Kang et al, 2016;He et al, 2020). These studies suggest that PODXL may be responsible for the impaired proliferative activity of SSC by TCF3 silencing.…”
Section: Podxl Is a Direct Target Of Tcf3 In Human Sscsmentioning
confidence: 83%
“…Those data suggest that TCF3 may influence the adhesion of human SSCs via different downstream targets compared to ESCs. It has been shown that PODXL is a pluripotent surface marker and enriched in many cancer cells (He et al, 2020), PODXL positive hematopoietic stem cells can reconstitute myeloid and lymphoid lineages in recipients with lethal radiation (Doyonnas et al, 2005). PODXL promotes cancer development and aggressiveness by activating MAPK and PIK3 pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Tyrosine phosphorylation of RUFY1 by ETK appears to be important for its endosomal localization and could play an important role promoting tumoral transformation by affecting downstream effectors of PI3-kinase. RUFY1 was also shown to interact with podocalyxin-like protein (PODXL), a transmembrane glycoprotein with anti-adhesive properties associated with poor prognosis of several cancers ( Taniuchi et al, 2018 ; He et al, 2020 ; Table 1 ). Gastric cancer progression is significantly increased upon PODXL expression, a phenotype reduced by concomitant RUFY1 silencing.…”
Section: Fyco1mentioning
confidence: 99%
“…Our understanding of the role of lncRNAs in the progression and suppression of multiple tumors has resulted in novel opportunities to improve the diagnosis and treatment of malignancies [ 17 , 18 ]. Meta-analyses revealed that HOXD-AS1[ 4 ], PODXL [ 19 ], and TP73-AS1 [ 20 ] were associated with the clinicopathological characteristics and prognosis of tumors. LncRNA prostate cancer-associated transcript 6 (PCAT6), which was first identified in keratinocytes, indirectly activates the Wnt/β-catenin pathway by interacting with KLHL12 in cervical cancer cells [ 21 ].…”
Section: Introductionmentioning
confidence: 99%